Analysis Antioxidant of Clove Leaves (Syzygium aromaticum) as a Source of Bioactive Compounds - Wael, Syahran; Arini, Ine; Muskita, Marike; Rakuasa, Heinrich (RUMPHIUS, 2026)
This study aimed to evaluate the antioxidant activity of the chloroform extract of clove leaves (Syzygium aromaticum) as a source of bioactive compounds. Unlike most previous studies that predominantly focused on essential oils or polar extracts of clove, this research specifically investigates the antioxidant potential of the semi-polar chloroform extract, which remains relatively underexplored. Extraction was performed using chloroform to obtain semi-polar compounds with potential biological activity. Phytochemical screening revealed the presence of phenolic compounds, flavonoids, tannins, and terpenoids, which are known to function as natural antioxidants. Antioxidant activity was assessed using the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay based on the ability of the sample to neutralize free radicals. The results demonstrated an increase in percentage inhibition with increasing extract concentration, indicating a positive linear relationship between concentration and antioxidant activity. Linear regression analysis yielded an IC₅₀ value of 69.40 ppm, classifying the extract as having strong antioxidant activity. In comparison, ascorbic acid exhibited an IC₅₀ value of 8.75 ppm, indicating very strong antioxidant activity. This difference is attributed to the nature of ascorbic acid as a pure compound, whereas the chloroform extract consists of a complex mixture of secondary metabolites. The novelty of this study lies in highlighting the significant antioxidant potential of the semi-polar chloroform fraction of clove leaves, thereby expanding the understanding of solvent-specific bioactive compound distribution and providing new insight into its possible application in functional food and pharmaceutical development. Overall, the findings suggest that the chloroform extract of clove leaves has promising potential as a natural source of bioactive compounds for further development.